CYP1A2 polymorphism and caffeine ingestion in relation to apoptosis markers after a resistance exercise in trained men: a randomized, double-blind, placebo-controlled, crossover study: Caffeine, CYP1A2 polymorphism and exercise-induced apoptosis - Rahimi, Mohammad Rahman; Faraji, Hassan; AL-Zangana, Tahseen Abdulkarim Amin; Khodamoradi, Maryam (Progress in Nutrition, 2020)
The objectives of this study was to determine the effects of caffeine ingestion and CYP1A2 polymorphism on Bax and Bcl-2 levels, as apoptosis markers, in acute resistance exercise (RE). In a randomized, double-blind, placebo-controlled, crossover study, fifteen trained men completed acute RE at 85% of 1RM. Subjects ingested either caffeine (CAF, 6 mg.kg−1 body mass) or placebo (PLA) one hour prior to exercise. Blood samples were taken pre-exercise (PRE), immediately post (POST), and 15 min (15 min POST) post RE for measurement of serum concentrations of Bax and Bcl-2 biomarkers. The CYP1A2 -163C>A polymorphisms were analyzed by amplification refractory mutation system–polymerase chain reaction (ARMS–PCR) in genomic DNA samples which were isolated from the whole blood samples. Subjects were classified as either AA (n= 8) or AC/CC genotypes (n=7). At POST, Bax concentrations were significantly higher in PLA AA than PRE (p=0.014), CAF AA (p=0.003), CAF AC/CC (p=0.039) and PLA AA (p=0.034). No significant changes were observed in Bcl-2 levels at POST compared to PRE in both groups of CAF or PLA (p>0.05). However, Bcl-2 levels in 15 min POST were significantly higher in CAF AA than CAF AC/CC (p=0.003). Change percent of Bax/Bcl-2 ratio were significantly higher in PLA AC/CC at POST when compared with CAF AA (p=0.002) or CAF AC/CC (p=0.007), and were significantly lower in CAF AA at 15min POST than PLA AA (p=0.039). The findings indicate that exercise alone could accelerate apoptosis in the AC/CC group, whereas caffeine appears to attenuate susceptibility of cells to apoptosis.